2016
DOI: 10.1038/srep32413
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic marine microbes influence the effects of climate change on a commercially important tropical bivalve

Abstract: There is growing evidence that climate change will increase the prevalence of toxic algae and harmful bacteria, which can accumulate in marine bivalves. However, we know little about any possible interactions between exposure to these microorganisms and the effects of climate change on bivalve health, or about how this may affect the bivalve toxin-pathogen load. In mesocosm experiments, mussels, Perna viridis, were subjected to simulated climate change (warming and/or hyposalinity) and exposed to harmful bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
1
18
2
Order By: Relevance
“…The highest concentrations of toxins quantified reach approximately 10% of action limit, thereby representing a low overall risk to shellfish consumers based on the data generated in this study. The recent work of Turner et al, (2016), showed evidence for low PST uptake (maximum 31 µg STX eq/kg) in mussels in mesocosms containing Alexandrium minutum at 100,000 cells/L held at conditions (temperature 28 o C and 32 o C; salinity 35 PSU and 31 PSU) similar to the environmental conditions recorded in Mangalore during this study ( Table S1). The highest concentrations were determined in oysters from Mulki and Sasthana, in comparison to the mussels from Gangoli and Someshwar.…”
Section: Discussionsupporting
confidence: 72%
“…The highest concentrations of toxins quantified reach approximately 10% of action limit, thereby representing a low overall risk to shellfish consumers based on the data generated in this study. The recent work of Turner et al, (2016), showed evidence for low PST uptake (maximum 31 µg STX eq/kg) in mussels in mesocosms containing Alexandrium minutum at 100,000 cells/L held at conditions (temperature 28 o C and 32 o C; salinity 35 PSU and 31 PSU) similar to the environmental conditions recorded in Mangalore during this study ( Table S1). The highest concentrations were determined in oysters from Mulki and Sasthana, in comparison to the mussels from Gangoli and Someshwar.…”
Section: Discussionsupporting
confidence: 72%
“…Climate change conditions have been reported experimentally to alter physiology of bivalves and interaction with HABs (Farrell et al, 2015;Turner et al, 2016). Therefore, the HABbivalve-pathogen interaction likely will evolve under future climate conditions.…”
Section: Discussion and Future Research Recommendationsmentioning
confidence: 99%
“…As similarly reported by participants in the NSF's IGERT program, benefits under the Gothenburg model have been tangible at the student, academic and institutional level (Carney et al, 2006). These benefits have included the successful completion of an interdisciplinary PhD thesis (Eriander, 2016), high impact disciplinespecific (e.g., Eriander et al, 2016;Infantes et al, 2016a, b;Kaur Kahlon et al, 2016;Turner et al, 2016;Kadfak and Knutsson, 2017) as well as interdisciplinary publications (Cole and Moksnes, 2016;Moksnes et al, 2016a, b), new successful interdisciplinary grant applications, and individual career progression.…”
Section: Discussionmentioning
confidence: 99%
“…In some sectors of the academic community suspicion of interdisciplinary working persists, with the notion often reported that this approach dilutes efforts away from the study of traditional disciplines (Rylance, 2015). At Gothenburg, while expanding our interdisciplinary pursuits, we have maintained our disciplinary integrities as evidenced by the publishing of intra-disciplinary studies (e.g., Eriander et al, 2016;Infantes et al, 2016a, b;Kaur Kahlon et al, 2016;Turner et al, 2016;Kadfak and Knutsson, 2017). When the Graduate School was established at Gothenburg we followed the same model as that underpinning the NSF's IGERT programs (Carney et al, 2006) with an emphasis on both interdisciplinary and intra-disciplinary outcomes.…”
Section: Discussionmentioning
confidence: 99%